Developing a Predictive Accreditation Simulator: A Strategic Quality Gateway for Private Universities in Indonesia - Bachri, Syaiful; Cahyadi, Eko Ruddy; Triyonggo, Yunus (Journal Public Policy, 2025)
The accreditation landscape for private universities under the oversight of LLDIKTI Wilayah III in Indonesia is characterized by significant disparities in institutional readiness and compliance with national standards. Current data highlight a pressing need for strategic intervention, as a considerable proportion of institutions remain within the "yellow" and "red" zones of accreditation preparedness. In response to this challenge, this study analyzes the critical factors influencing the effectiveness of accreditation facilitation and formulates evidence-based strategies for its enhancement. Employing a mixed-methods approach, the research integrates comprehensive accreditation mapping, stakeholder interviews, and multi-layered analytical frameworks, including Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT, and the Analytical Hierarchy Process (AHP). The findings identify organizational commitment and institutional readiness as the most determinants of accreditation success, with internal quality assurance units acting as pivotal actors. Consequently, the study proposes the development of a predictive accreditation simulator, designed to align with specific institutional typologies and internal quality assurance systems. Conceptualized as a strategic quality gateway, this tool is intended to enable proactive readiness assessment, foster continuous improvement, and strengthen institutional resilience. Ultimately, it aims to ensure consistent alignment with national standards and promote sustainable quality assurance practices within Indonesia's private higher education sector.